Development Of Student Worksheets With A Contextual Approach To Quadrilateral And Triangular Material - Fidyawati, Devy; Musa, Lisa Aditya Dwiwansyah; Yusuf, Munir (Prodi Pendidikan Matematika FTIK IAIN Palopo, 2022)
Abstract:This research attempted to: find out how the student worksheet development with a contextual approach; to find out the result of the student worksheet development with a contextual approach meets valid and practical categories. The research methodology utilized Research and Development that focused on developing student worksheets with a contextual approach. This development applied Borg and Gall design model. The developing worksheet materials were rectangles and triangles. The obtained data comes from the validation results by four validators, students' responses, and a literature review. The research site is in one of the SMP Negeri in the city of Palopo. The validation result of student worksheets with a contextual approach was: (1) the material expert score is 90% is in a very valid category, (2) the media expert score is 85% is in a very valid category, (3) design expert score is 83% is in a very valid category. Student worksheets with a contextual approach are also in a very practical category at 87%. Abstrak:Penelitian ini tentang pengembangan Lembar Kerja Siswa (LKS) dengan pendekatan kontekstual yang memenuhi kategori valid dan praktis. Penelitian pengembangan ini menggunakan desain Borg and Gall. Materi LKS yang dikembangkan adalah segi empat dan segitiga. Data diperoleh dari hasil validasi empat validator, respon siswa, dan studi pustaka. Lokasi penelitian berada di salah satu SMP Negeri di kota Palopo. Hasil validasi LKS menunjukkan: (1) ahli materi dengan skor 90% berada pada kategori sangat valid, (2) ahli media dengan skor 85% berada pada kategori sangat valid, (3) desain ahli dengan skor 83% berada pada kategori sangat valid. LKS dengan pendekatan kontekstual juga berada pada kategori sangat praktis dengan skor 87%.